THE SEMANTIC- PRAGMATIC MEANING OF THE SENTENCE - Tuhtaeva Shahzoda Oktamovna, (TADQIQOTLAR, 2025)
Abstract:    This  work  is  based  on  the  linguistic  distinction,  especially,  from semantic  and  pragmatic  directions,  and  the  application  of  the  semantic-  pragmatic distinctions.